(untitled) (Commonwealth Journal of Local Governance, 2019)
After briefly defining participatory budgeting and reviewing its evolution worldwide and Commonwealth expansion over the last three decades, this paper explores the potential it holds for contributing to the achievement of the United Nations’ Sustainable Development Goals. Its looks especially at how participatory budgeting is contributing to the achievement of SDG 16 and provides some specific recommendations for action, based on innovative practice examples from around the world, highlighting how practice across diverse local authorities could be used to monitor target 16.7 ‘to ensure responsive, inclusive, participatory and representative decision-making at all levels.’